Two novel parameters to evaluate the global complexity of the Sun's magnetic field and track the solar cycle - Zhao, Liang (author); Landi, E. (author); Gibson, Sarah (author) (The Astrophysical Journal, 2013)
Since the unusually prolonged and weak solar minimum between solar cycles 23 and 24 (2008-2010), the sunspot number is smaller and the overall morphology of the Sun's magnetic field is more complicated (i.e., less of a dipole component and more of a tilted current sheet) compared with the same minimum and ascending phases of the previous cycle. Nearly 13 yr after the last solar maximum (˜2000), the monthly sunspot number is currently only at half the highest value of the past cycle's maximum, whereas the polar magnetic field of the Sun is reversing (north pole first). These circumstances make it timely to consider alternatives to the sunspot number for tracking the Sun's magnetic cycle and measuring its complexity. In this study, we introduce two novel parameters, the standard deviation (SD) of the latitude of the heliospheric current sheet (HCS) and the integrated slope (SL) of the HCS, to evaluate the complexity of the Sun's magnetic field and track the solar cycle. SD and SL are obtained from the magnetic synoptic maps calculated by a potential field source surface model. We find that SD and SL are sensitive to the complexity of the HCS: (1) they have low values when the HCS is flat at solar minimum, and high values when the HCS is highly tilted at solar maximum; (2) they respond to the topology of the HCS differently, as a higher SD value indicates that a larger part of the HCS extends to higher latitude, while a higher SL value implies that the HCS is wavier; (3) they are good indicators of magnetically anomalous cycles. Based on the comparison between SD and SL with the normalized sunspot number in the most recent four solar cycles, we find that in 2011 the solar magnetic field had attained a similar complexity as compared to the previous maxima. In addition, in the ascending phase of cycle 24, SD and SL in the northern hemisphere were on the average much greater than in the southern hemisphere, indicating a more tilted and wavier HCS in the north than the south, associated with the early reversal of the ...